2018
DOI: 10.5334/gjgl.592
|View full text |Cite
|
Sign up to set email alerts
|

Self-embedding and complexity in oral registers

Abstract: This article reports the results of a study on the self-embedding depth of nominal, verbal and clausal projections in spoken corpora of German. We compared two spoken registers featuring public and non-public (i.e. private) conversation by measuring the depth of self-embedding in C, V, and N projections. The findings confirm the hypothesis that the familiarity of the speech situation (public vs. non-public speech) has a significant impact on complexity in terms of self-embedding: speakers use more self-embeddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Spoken registers include broadcasts (Zhang et al, 2017), public and non-public conversation (Verhoeven & Lehmann, 2018), and television programs (Sardinha & Pinto, 2021). For example, Sardinha and Pinto (2021) analyzed American television programs and found that all the programs can be categorized into different specific registers, such as ''presentation of information, opinion, and discussion,'' and so on.…”
Section: Main Research Themesmentioning
confidence: 99%
“…Spoken registers include broadcasts (Zhang et al, 2017), public and non-public conversation (Verhoeven & Lehmann, 2018), and television programs (Sardinha & Pinto, 2021). For example, Sardinha and Pinto (2021) analyzed American television programs and found that all the programs can be categorized into different specific registers, such as ''presentation of information, opinion, and discussion,'' and so on.…”
Section: Main Research Themesmentioning
confidence: 99%